No. 3n is not a factor of 3n + 7.
No. 3n is not a factor of 3n + 7.
No. 3n isn't a factor of 3n + 7. The GCF of 3n + 7 and 9n is 1.
The GCF is 3n.
If that's +25, that factors to (3n - 5)(3n - 5) or (3n - 5)2
Yes. 3n2/12n3 = 1/4n
The first, second, third, fourth, and fifth terms of 3n - 7 are as follows:1: -42: -13: 24: 55: 8
3n+2 + (3n+3 - 3n+1) = 3n+1+1 + (3n+1+2 - 3n+1) = 3*3n+1 + (9*3n+1 - 3n+1)= (3+9-1)*3n+1 = 11*3n+1.
(9n2 - 121) = (3n + 11) (3n - 11)
1/3n
1/3n
8
(3n)(3n-1) = 3n * 3n - 3n * 1 Now, perform the multiplication: (3n * 3n) = 9n^2 (3n * 1) = 3n So, (3n)(3n-1) simplifies to: 9n^2 - 3n
3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6
The expression 3n times 3n can be simplified by multiplying the coefficients (3 * 3) and adding the exponents (n + n). This results in 9n^2, where n is raised to the power of 2. This simplification follows the rules of exponentiation, specifically the rule that states when multiplying two terms with the same base, you add the exponents.
Is it a. 3n square and 3n ans. 3n b. 3n *2 and 3n ans.3n ans. 3n for both!!
(8m - 3n)^2 I assume you mean 'squared' , when you write 'square 2'. Because means raising to the power of '2'. Whereas 'cubing' means raising to the power of '3'. To answer (8m - 3n)(8m - 3n( = 64m^2 - 24mn - 24 mn + 9n^2 = 64m^2 - 48 mn + 9n^2 Done!!!!